Search for W ' bosons decaying to a top and a bottom quark at root s=13 TeV in the hadronic final state - (:unkn) unknown (ELSEVIER, 2021)
A search is performed for W ' bosons decaying to a top and a bottom quark in the all-hadronic final state, in proton-proton collisions at a center-of-mass energy of 13TeV. The analyzed data were collected by the CMS experiment between 2016 and 2018 and correspond to an integrated luminosity of 137fb(-1). Deep neural network algorithms are used to identify the jet initiated by the bottom quark and the jet containing the decay products of the top quark when the W ' boson from the top quark decays hadronically. No excess above the estimated standard model background is observed. Upper limits on the production cross sections of W ' bosons decaying to a top and a bottom quark are set. Both left- and right-handed W ' bosons with masses below 3.4TeV are excluded at 95% confidence level, and the most stringent limits to date on W ' bosons decaying to a top and a bottom quark in the all-hadronic final state are obtained. (C) 2021 The Author(s). Published by Elsevier B.V.
Keywords: CMS; W ' search; Top resonances; Boosted top